MCSE : Exchange 2000 Server administration - Glenn, Walter J. (Sybex, 2001)
Here’s the book you need to prepare for Exam 70-224, Installing, Configuring, and Administering Microsoft Exchange 2000 Server: Full coverage of every exam objective—all the information you need to know; Practical information on installing, configuring, and administering Exchange 2000 Server; Hundreds of challenging review questions, in the book and on the CD; Leading-edge exam preparation software, including a testing engine, simulation software, and electronic flashcards